(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article explores and analyzes the category of social danger of the act in the theory of criminal law, specifically focusing on the degree and nature of the social danger of embezzlement by plundering. The opinions of leading scholars in this field have been studied and analyzed, and the author expresses opinions on determining the degree and nature of the social danger of embezzlement by plundering.